Coping mediates the effects of cognitive–behavioral therapy for alcohol use disorder among out‐patient clients in Project MATCH when dependence severity is high. (22nd May 2017) - Roos, Corey R.; Maisto, Stephen A.; Witkiewitz, Katie
Abstract: Background and aims: There is inconsistent evidence that alcohol‐specific coping is a mechanism of change in cognitive–behavioral therapy (CBT) for alcohol use disorder (AUD). Our primary aim was to test whether baseline dependence severity moderates the mediational effect of CBT on drinking outcomes via coping. Design: Secondary data analysis of Project MATCH1, a multi‐site alcohol treatment trial in which participants, recruited in out‐patient and aftercare arms, were randomized to three treatments: CBT, motivational enhancement therapy (MET) and Twelve‐Step facilitation (TSF). Setting: Nine research sites in the United States. Participants: A total of 1063 adults with AUD. Measurements: The primary outcomes were percentage days abstinent and percentage heavy drinking days at the 1‐year follow‐up. Coping was assessed with the Processes of Change Questionnaire2 . Dependence severity was measured with the Alcohol Dependence Scale3 . Findings: Among the full available sample (across treatment arms), there were no significant moderated mediation effects. Double moderated mediation analyses indicated that several moderated mediation effects were moderated by treatment arm (all P  < 0.05). In the out‐patient arm, there were several significant moderated mediation effects (all P  < 0.05), but no significant moderated mediation effects in the aftercare arm. For out‐patient clients with high baseline dependence severity, end‐of‐treatment coping mediated the positive treatment effects of CBT, compared with both MET and TSF, on 1‐year drinking outcomes (all P  < 0.05). Coping did not mediate treatment effects of CBT among those with low or moderate dependence severity. Conclusions: In the Project MATCH out‐patient sample, whether or not coping mediated the effects of cognitive–behavioral therapy for alcohol use disorder was conditional on dependence severity. End‐of‐treatment coping mediated the positive treatment effects of cognitive–behavioral therapy on 1‐year drinking outcomes among out‐patient clients when dependence severity was high, but not when dependence severity was low or moderate.